'Dominoes' - Adriaanse, Jacobus Petrus (2012)
The main component of this dissertation is a creative project and screenplay for a full feature film called 'Dominoes'. It follows the story of an unnamed teacher (referred to in the screenplay only as V) from one of Cape Town's lower income neighborhoods, who, when faced by the gradual and then sudden brutalizing effects of crime on his community and on him personally, become a vigilante. He haphazardly targets his local crime hierarchy, confronting them with the same destructive violence that they terrorize the community with. As things escalate, his friend, a local policeman, as well as one of his students, are drawn into the battle and become entangled in the carnage, thereby altering the course of the vigilante's crusade as he has to juggle friendship, loyalty and duty while navigating this new and dangerous terrain. Additionally I includes a research paper: 'The Fine Line between Vigilance and Anarchy - Unravelling the Paradox of Vigilantism'. This paper broadly outlines the phenomena of vigilantism, drawing on research from experts as well as examples from real life